Recurrent urinary retention due to seminal vesicle cyst a report of rare entity - Yazan Al-Dali (17019150) (2023)
Male pelvic cyst rarely causes symptoms; here, we are presenting a case of a 48-year-old gentleman who presented with acute urinary retention stemming from a pelvic cyst. This presentation has been recurrent despite undergoing repeated TRUS aspiration of the cyst to relieve the symptoms. We performed a robotic pelvic cyst excision with peritoneal window in an attempt to cure the patient. Based on the MRI and histopathology, it was likely a seminal vesicle cyst that is causing these recurrent episodes. On 3 months follow-up, the patient was symptom free without any complaints. Other Information Published in: Urology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eucr.2023.102556